Formulation and evaluation of natural lip balm: exploring the synergistic benefits of beetroot and Kaempferia galanga Linn - Che Radzi, Nurhaslina; Ahmad Kamarul, Afiqah Dayana (Universiti Teknologi MARA Shah Alam, 2025)
Growing consumer concern over synthetic additives has intensified interest in plant-based lip care. This study formulated and evaluated a dual-extract lip balm using beetroot (Beta vulgaris) pigment and Kaempferia galanga Linn (KGL) essential oil as natural colourant and bioactive agents. Twenty-two formulations were prepared from coconut oil, beeswax, and candelilla wax, with varying beetroot:KGL ratios (0.5–2.5 g). Each formulation was assessed for pH (n=3), melting point, greasiness index, surface homogeneity, and accelerated colour stability (30 days at 40 °C/75 % RH and 4 °C). Among all tested formulations, F7 exhibited the most favourable balance of non-greasy texture, stable pH, and good melting point, supporting its potential as a safe and natural cosmetic alternative.